Vegetative Insecticidal Protein (Vip): A Potential Contender From Bacillus thuringiensis for Efficient Management of Various Detrimental Agricultural Pests - Gupta, Mamta; Kumar, Harish; Kaur, Sarvjeet (Frontiers in Microbiology, 2021)
Bacillus thuringiensis (Bt) bacterium is found in various ecological habitats, and has natural entomo-pesticidal properties, due to the production of crystalline and soluble proteins during different growth phases. In addition to Cry and Cyt proteins, this bacterium also produces Vegetative insecticidal protein (Vip) during its vegetative growth phase, which is considered as an excellent toxic candidate because of the difference in sequence homology and receptor sites from Cry proteins. Vip proteins are referred as second- generation insecticidal proteins, which can be used either alone or in complementarity with Cry proteins for the management of various detrimental pests. Among these Vip proteins, Vip1 and Vip2 acts as binary toxins and have toxicity towards pests belonging to Hemiptera and Coleoptera orders, whereas the most important Vip3 proteins have insecticidal activity against Lepidopteran pests. These Vip3 proteins are similar to Cry proteins in terms of toxicity potential against susceptible insects. They are reported to be toxic towards pests, which can not be controlled with Cry proteins. The Vip3 proteins have been successfully pyramided along with Cry proteins in transgenic rice, corn, and cotton to combat resistant pest populations. This review provides detailed information about the history and importance of Vip proteins, their types, structure, newly identified specific receptors, and action mechanism of this specific class of proteins. Various studies conducted on Vip proteins all over the world and the current status have been discussed. This review will give insights into significance of Vip proteins as alternative promising candidate toxic proteins from Bt for management of pests in most sustainable manner.